Structure of volcano plumbing systems: A review of multi-parametric effects - TIBALDI, ALESSANDRO (Journal of Volcanology and Geothermal Research, 2015)
Magma is transported and stored in the crust mostly through networks of planar structures (intrusive sheets), ranging from vertical dykes to inclined sheets and horizontal sills, and magma chambers, which make up the plumbing system of volcanoes. This study presents an overview of plumbing systems imaged at different depths and geodynamic settings, in order to contribute to assessing the factors that control their geometry. Data were derived from personal field surveys and through the analysis of publications; observations include local lithology and tectonics of the host rock with special reference to local fault kinematics and related stress tensor, regional tectonics (general kinematics and far-field stress tensors), geology and shape of the volcano, topographic settings, and structural and petrochemical characteristics of the plumbing system. Information from active volcanoes and eroded extinct volcanoes is discussed; the shallow plumbing system of active volcanoes has been reconstructed by combining available geophysical data with field information derived from outcropping sheets, morphometric analyses of pyroclastic cones, and the orientation and location of eruptive fissures. The study of eroded volcanoes enabled to assess the plumbing system geometry at deeper levels in the core of the edifice or underneath the volcano-substratum interface. Key sites are presented in extensional, transcurrent and contractional tectonic settings from North and South-America, Iceland, the Southern Tyrrhenian Sea and Africa. The types of sheet arrangements illustrated include swarms of parallel dykes, diverging rift patterns, centrally-inclined sheets, ring and radial dykes, circum-lateral collapse sheets, sills, and mixed members. This review shows that intrusive sheet emplacement at a volcano depends upon the combination of several local and regional factors, some of which are difficult to be constrained. While much progress has been made, it is still very challenging to forecast the likely paths and geometry of sheet ...